Clinicians' Perspectives on a Web-Based System for Routine Outcome Monitoring in Old-Age Psychiatry in the Netherlands - Veerbeek, Marjolein A; Oude Voshaar, Richard C; Pot, Anne Margriet (JMIR Publications, 2012)
BackgroundIn health care, the use of physical parameters to monitor physical disease progress is common. In mental health care, the periodic measurement of a client's functioning during treatment, or routine outcome monitoring, has recently become important. Online delivery of questionnaires has the potential to reduce clinicians' resistance to the implementation of routine outcome monitoring. Online delivery enables clinicians to receive results on a questionnaire in a graphic directly after data entry. This gives them insight into the progress of a client at a single glance. ObjectiveTo explore clinicians' perspectives on a routine outcome monitoring procedure where questionnaires and feedback on scores were delivered online. Questionnaires could also be filled out on paper and then entered into the online system by a research assistant. MethodsIn 2009 we sent an online survey, consisting of five yes-or-no questions and six open-ended questions, to all clinicians in the 14 mental health care organizations working with the routine outcome monitoring system in the Netherlands. Of the 172 clinicians contacted, 80 (47%) opened the link and 70 of these 80 (88%) clinicians completed the survey. ResultsClinicians seldom used the graphical feedback from the Web-based system, which indicates that direct feedback on scores did not enhance the implementation of routine outcome monitoring. Integration into the electronic patient record and more training on interpretation and implementation of feedback in daily practice were seen as the primary points for further improvement. It was mainly the availability of a research assistant that made the routine outcome monitoring procedure feasible. ConclusionsWithout a research assistant and training in the interpretation of outcomes, software programs alone cannot ensure effective implementation of monitoring activities in everyday practice.